Europe favors United Air Traffic Control system. - Weiss, G. (IEEE spectrum)
For the last 40 years, European air traffic control has been managed by Eurocontrol. (Brussels), an organization made up of 31 European states, including the countries of the European Union. Single Sky was launched in 1999 with the idea of combining the legislative weight of the European Union with Eurocontrol's operational and technical expertise. Under the plan, the patchwork of national zones will be merged into a single region with a single set of rules. Airspace will be reconfigured to follow the flow of traffic instead of national borders and to reduce the number of handovers. Civilian and military airspace will be better integrated. And equipment and systems will be harmonized. There is opposition to this plan which centre on military airspace and the roles of the European Union and Eurocontrol.